2015
DOI: 10.1016/j.jveb.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative bedding substrates on lamb welfare, productive performance, and meat quality during the finishing phase of fattening

Abstract: Keywords:bedding substrates welfare social behaviors stereotypies meat quality a b s t r a c tThe study analyzed the effect of using sawdust, cellulose, straw, and rice husk bedding on the welfare, performance and meat quality of lambs during the finishing phase of fattening. Ninety-six lambs (fed ad libitum with concentrate) were assigned to pens containing 1 of 4 bedding materials in groups of 12 for 14 days. Live weight and feed consumption were recorded to estimate daily gain and conversion index, and carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
3
6
0
2
Order By: Relevance
“…Under this condition the ewes and lambs prefer expose their head outside of the pen looking for fresh air. Some authors have reported a negative relationship between lamb stereotypes frequency and productive performance (Aguayo-Ulloa et al 2015aTeixeira et al 2015). In the present trial, the welfare of the lambs was not evaluated.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Under this condition the ewes and lambs prefer expose their head outside of the pen looking for fresh air. Some authors have reported a negative relationship between lamb stereotypes frequency and productive performance (Aguayo-Ulloa et al 2015aTeixeira et al 2015). In the present trial, the welfare of the lambs was not evaluated.…”
Section: Resultsmentioning
confidence: 82%
“…In the present trial, the welfare of the lambs was not evaluated. It is important to evaluate the effect of the housing (RFC and FP) on animal welfare, to know the behavioural and physiological profiles associated with the stress of the animals during the fattening period, as reported by some authors (Teixeira et al 2012(Teixeira et al , 2015Aguayo-Ulloa et al 2015aPascualAlonso et al 2015). Is it possible to improve the performance of the lambs in RFC system if the stoking pen is increased or if the environment is enriched?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Esto favorece la utilización de materiales absorbentes como la paja en solera [17]. Teixeira, et al [18] utilizaron otros materiales como serrín o cáscara de arroz en el suelo, sin obtener diferencias en el rendimiento de los corderos. Muñoz-Osorio, et al [19] compararon un sistema de slat de plástico o metal con un suelo de hormigón para engorde de corderos machos en intensivo, registrando mayores rendimientos productivos cuando se empleó el slat, si bien con una fuerte dependencia de otros factores (alimentación, condiciones climáticas, etc.…”
Section: Introductionunclassified